The Efficacy of Traditional Cognitive Behavioural Therapy for Depressed Adults with Anhedonia: A Systematic Review - Tran Ngoc Huu (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
To date, the impact of traditional cognitive behavioural therapy (CBT) on anhedonia in major depressive disorder (MDD) has yet been systematically evaluated. This systematic review aims to examine the efficacy of traditional CBT for depressed adults with anhedonia. A literature search for randomised controlled trials of traditional CBT in adults with MDD from inception to July 2020 was conducted in 8 databases. The primary outcome was the levels of anhedonia. Ten studies with adults with MDD met the eligibility criteria. Our results indicate that traditional CBT is as effective as euthymic therapy, positive psychology therapy, self-system therapy,and medications for anhedonia in depression. Besides, our data provide further support for the development of augmented CBT to optimise treatment outcome for depressed adults with anhedonia. Received 11th June 2021; Revised 2nd September 2021; Accepted 20th September 2021